Optimalisasi Komunikasi Pemerintah Desa dalam Sosialisasi Identitas Kependudukan Digital (IKD): Studi Kasus di Desa Kota Batu - Ivana Ismia Anwar; Undang Suryatna; Ali Alamsyah Kusumadinata (Journal of Innovative and Creativity, 2025)
This study examines the communication implemented by the Kota Batu Village Government in socializing the Digital Population Identity (IKD) program to the community, and analyzes its effectiveness and the constraints encountered. The transformation of population administration towards digitalization through IKD aims to improve the efficiency of public services. Using a qualitative descriptive approach, this research was conducted at the Kota Batu Village Office with key informants from village operators and supporting informants from district/sub-district operators, RT/RW heads, and IKD user residents. Data collection techniques included observation, semi-structured interviews, and documentation, which were then analyzed using the Miles and Huberman model. The findings indicate that the Kota Batu Village Government employed three main communication: direct interpersonal approach at the village office (when residents handled administrative affairs), utilization of community social forums (such as posyandu and community meetings), and dissemination of information through digital media (RT WhatsApp groups and village Instagram). The interpersonal strategy proved to be the most effective as it allowed for two-way communication, direct demonstrations, and personal assistance, which greatly helped residents understand and activate their IKD, including identifying mobile phone specification issues. However, socialization through social forums and digital media was less effective due to a lack of detailed procedural information and technical device requirements, as well as minimal interaction. Key constraints faced included low digital literacy among the community, uneven access to technology (including poorly communicated smartphone compatibility issues), limited accompanying human resources, low public interest and perception of urgency, and reliance on passive communication. This study concludes that the effectiveness of IKD socialization highly depends on the village government's ability to adapt participatory, comprehensive, and proactive communication strategies to overcome community's technical and psychosocial barriers.